Kebutuhan Media M-Learning Berbasis Android - Fhela Vhantoria Ningrum (Universitas Cokroaminoto Palopo, 2023)
The problem of this research is the low social arithmetic score of class VII students of MTs Negeri 1 North Lampung of 82.10% under the maximum completeness criterion of 70. So a solution to this problem is sought by analyzing student needs. The purpose of the study aims to analyze the needs of students on Android-based M-Learning media. The method used is descriptive exploratory. The research was conducted on March 21, 2022, with 33 class VII students at MTs Negeri 1 Kotabumi as subjects. The research subjects were randomly selected. The data in this study is in the form of an Android-based M-Learning media needs questionnaire. The findings of this study are that students think that social arithmetic is an important but difficult subject to understand. Difficulties in understanding social arithmetic are indicated due to the lack of available learning resources. Furthermore, regarding the learning strategies or techniques used by the teacher in the learning process, students want material. Discussion regarding the analysis of student needs requires learning resources for social arithmetic material in the form of media that can be visualized with moving animation. In addition, it can be packaged and accessed easily on each student's gadget. Android-based M-learning can accommodate all of that, where social arithmetic material is made in an attractive animated form with complete components in it. Components in the form of learning objectives, basic competencies, questions, and exercises. Android-based M-learning is in the form of an application that can then be installed and accessed free of charge by students. The conclusion is that it is necessary to develop Android-based M-Learning media at MTs Negeri 1 Kotabumi